Synonymies, transferences and redescriptions in Neotropical Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) - Monné, Miguel A. (Zootaxa, 2020)
A new synonymy is proposed for Anisopodesthes Melzer, 1931 (junior synonym of Lathroeus Thomson, 1864), with the consequent new combination for Lathroeus zikani (Melzer, 1931). The following species are transferred from Nealcidion Monné, 1977 to Lathroeus: L. decoratus (Melzer, 1932), comb. nov. (= Alcidion decoratum); L. interrogationis (Bates, 1863), comb. nov. (= Alcidion interrogationis); and L. simillimus (Melzer, 1932), comb. nov. (= Alcidion simillimum). Moreover, a key for the species of Lathroeus is provided and the unknown female of L. zikani is described for the first time.